Everything you need to know about STDs (sexually transmitted diseases) - Woods, Samuel G. (New York : Rosen Pub. Group, 2003)
This book describes sexually transmitted diseases, including AIDS, syphilis, gonorrhea, and genital herpes, and discusses their medical dangers and their treatments.
Includes index.
Includes glossary.
Includes bibliography.
9-12
Keywords: Sexually transmitted diseases